2020
DOI: 10.1038/s41598-020-64029-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-vector-borne transmission of lumpy skin disease virus

Abstract: The transmission of "lumpy skin disease virus" (LSDV) has prompted intensive research efforts due to the rapid spread and high impact of the disease in recent years, especially in eastern europe and Balkan countries. in this study, we experimentally evaluate the vaccine-derived virulent recombinant LSDV strain (Saratov/2017) and provide solid evidence on the capacity of the virus for transmission in a vectorproof environment. In the 60-day long experiment, we used inoculated bulls (IN group) and two groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…Recombinants may influence LSDV transmission also at another level. Indirect non-vectored transmission has always been considered to be of minor importance [75] but recent experiments with a recombinant LSDV strain demonstrated the possibility of contact transmission [76]. Whether this contact transmission was solely due to the recombinant nature of the used LSDV challenge strain needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinants may influence LSDV transmission also at another level. Indirect non-vectored transmission has always been considered to be of minor importance [75] but recent experiments with a recombinant LSDV strain demonstrated the possibility of contact transmission [76]. Whether this contact transmission was solely due to the recombinant nature of the used LSDV challenge strain needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, poxvirus infection can also occur through ingestion, parenteral inoculation, or droplet or aerosol exposure to mucous membranes or broken skin. Some poxviruses can be transmitted by fomites (inanimate objects) [ 43 ]. For example, studies have revealed that sheeppox and goatpox viruses are predominantly transmitted via aerosols [ 44 ]; whereas poxviruses from the genus Parapoxvirus can pass from one animal to another through direct or indirect contact.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the first recombinant LSDV Russia/Saratov/2017 was isolated from a bovine of a backyard farm in Saratov, close to the border with Kazakhstan, by Russian scientists. Later, the same research group provided experimental data on the virulence of this isolate [ 19 ] and also identified the second recombinant virus, LSDV Russia/Udmurtiya/2019, genetically close but still different from the first one. The study on the Russian recombinant LSDVs pointed out the potential role of illegal use of LSDV vaccines.…”
Section: Vaccine Side Effects and Safetymentioning
confidence: 99%
“…Direct contact [ 19 ] and seminal [ 20 ] transmission have been demonstrated experimentally, along with intrauterine transmission in the field [ 21 ]. Early observations have also supported the transmission of the virus via contaminated feed and water [ 11 ].…”
Section: Introductionmentioning
confidence: 99%